MINERALOGICAL AND CHEMICAL CHARACTERISTICS OF SPODOSOLS IN TOBA HIGHLAND, NORTH SUMATRA - B. H. Prasetyo (Indonesian Journal of Agricultural Science, 2009)
Spodosols are problem soils due to coarse texture, acid soil reaction, low nutrient status, and low soil moisture retention. About 2.16 million ha of Spodosols (1.1% of the Indonesianland areas) distributed in lowland and highland areas in Kalimantan, Sumatra, Sulawesi, and Papua. Spodosols of the Toba highland areas require special attention because theseforested lands are gradually cleared, but then abandoned because they are not suitable for agricultural development, causing land degradation. This study aimed to evaluate mineralogical and chemical characteristics of Toba highland Spodosols, North Sumatra, and their implication on agricultural development. Three pedons of the Toba highland Spodosols from Humbang Hasundutan regency were studied, consisted of soils developed from volcanic sand overlying liparite tuff under the influence of low temperature and high rainfall. Field observation was conducted in January 2008. Fifteen soil samples were collected from the three pedons based on the depth of soil horizon. Results indicated that the formation of these Spodosols were influenced by parent material, high elevation (1676-1821 m) above sea level), and by high amount of rainfall (2167 mm). The Spodosols in Toba highland were still in the early stage of development as characterized by shallow effective soil depth(22-23 cm), domination of weatherable minerals (39-81%) in the sand fraction and dominated by amorphous mineral as shown by sum of A1 + 1/2 Fe extracted by ammonium oxalate as much as 0.6-12.8%. The Spodosols were also characterized by coarse texture (66-95% sand fraction in E and B horizons), high organic-C content (1.4-37.7%), acid soil reaction (pH 3.7- 5.3), very high K2O in Oa horizon (552-933 mg kg-1) and B spodic or C horizon (812-2028 mg kg-1), and low base saturation (< 5%). The existence of biological processes in the surface layer was indicated by accumulation of exchangeable bases(0.88-1.14 cmolc kg-1 in Oa horizon and 0.09-0.25 cmolc kg-1 in B horizon), P2O5 (181-298 mg kg-1 in Oa horizon and 3-24 mg kg-1 in E horizon), and K2O (552-933 mg kg-1 in Oa horizon and 13- 30 mg kg-1 in E horizon). However, these nutrients were easilyleached after deforestation. With the sandy texture, loose structure, and no vegetation cover, the erosion hazard is high in the deforested areas. Therefore, lands with Spodosols of the Toba highland, especially are not recommended for agricultural development, rather they should be kept as forest lands.